Altered T‐cell subset distribution in the viral reservoir in HIV‐1‐infected individuals with extremely low proviral DNA (LoViReTs). (28th March 2022) - Gálvez, Cristina; Urrea, Víctor; Garcia‐Guerrero, Maria del Carmen; Bernal, Sílvia; Benet, Susana; Mothe, Beatriz; Bailón, Lucía; Dalmau, Judith; Martinez, Andrea; Nieto, Aroa; Leal, Lorna; García, Felipe; et al.
Abstract: Background: HIV cure strategies aim to eliminate viral reservoirs that persist despite successful antiretroviral therapy (ART). We have previously described that 9% of HIV‐infected individuals who receive ART harbor low levels of provirus (LoViReTs). Methods: We selected 22 LoViReTs matched with 22 controls ART suppressed for more than 3 years with fewer than 100 and more than 100 HIV‐DNA copies/10 6 CD4 + T cells, respectively. We measured HIV reservoirs in blood and host genetic factors. Fourteen LoViReTs underwent leukapheresis to analyze replication‐competent virus, and HIV‐DNA in CD4 + T‐cell subpopulations. Additionally, we measured HIV‐DNA in rectum and/or lymph node biopsies from nine of them. Results: We found that LoViReTs harbored not only lower levels of total HIV‐DNA, but also significantly lower intact HIV‐DNA, cell‐associated HIV‐RNA, and ultrasensitive viral load than controls. The proportion of intact versus total proviruses was similar in both groups. We found no differences in the percentage of host factors. In peripheral blood, 71% of LoViReTs had undetectable replication‐competent virus. Minimum levels of total HIV‐DNA were found in rectal and lymph node biopsies compared with HIV‐infected individuals receiving ART. The main contributors to the reservoir were short‐lived transitional memory and effector memory T cells (47% and 29%, respectively), indicating an altered distribution of the HIV reservoir in the peripheral T‐cell subpopulations of LoViReTs. Conclusion: In conclusion, LoViReTs are characterized by low levels of viral reservoir in peripheral blood and secondary lymphoid tissues, which might be explained by an altered distribution of the proviral HIV‐DNA towards more short‐lived memory T cells. LoViReTs can be considered exceptional candidates for future interventions aimed at curing HIV. Abstract :